Implementasi Supervisi Klinis Berbasis Lesson Study dalam Meningkatkan Kinerja Guru di SD Negeri Bangkeh Kecamatan Geumpang Kabupaten Pidie - Andayani, Andayani; Rita Novita; Zahraini, Zahraini (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research aims to find out whether the implementation of lesson study-based clinical supervision can improve the performance of Bangkeh State Elementary School teachers, Geumpang District, Aceh Pidie Regency. The research subjects were 8 teachers at Bangkeh State Elementary School, Geumpang District, Pidie Regency. Subjects are determined by the total sample or saturated sample. The research instruments used to determine teacher performance competency are interview guidelines, observation and documentation. This research uses school action research with two cycles. The research results showed that the teacher's performance in preparing the Learning Implementation Plan (RPP) after clinical supervision based on lesson study in the first cycle was in the adequate category with a score of 73.43 and in the second cycle it had increased to the good category with a score of 86.46. The teacher's performance in implementing learning in the first cycle was in the adequate category with a score of 70.04 and in the second cycle it increased to the good category with a score of 86.90. Based on the research results, it can be concluded that the performance of teachers at the Bangkeh State Elementary School, Geumpang District, Pidie Regency in planning the implementation of learning and implementing learning can be improved through the implementation of Lesson Study Based Clinical Supervision.